Thrombocytosis in splenic trauma: In-hospital course and association with venous thromboembolism. Issue 1 (January 2017) - Chia, Tze L.; Chesney, Tyler R.; Isa, David; Mnatzakanian, Gevork; Colak, Errol; Belmont, Caio; Hirpara, Dhruvin; Veigas, Precilla V.; Acuna, Sergio A.; Rizoli, Sandro; Rezende-Neto, Joao
Abstract: Introduction: Thrombocytosis is common following elective splenectomy and major trauma. However, little is known about the in-hospital course of platelet count (PC) and incidence of thrombocytosis after splenic trauma. Extreme thrombocytosis (PC > 1000 × 10 9 ) is associated with increased risk of venous thromboembolism (VTE) in primary thrombocytosis leading to the use of acetylsalicylic acid (ASA) for risk reduction, but the need for this agent in splenic trauma is undefined. Methods: Retrospective cohort study of all patients with splenic trauma between April 1, 2010 and March 31, 2014. The in-hospital course of PC was assessed based on splenic injury management type. The association of management type with thrombocytosis was evaluated using a multivariable logistic regression model adjusting for potential confounders. The association of thrombocytosis, extreme thrombocytosis, and ASA use for the outcome of VTE was explored. Results: 156 patients were eligible, PC initially increased in all patients with the highest peak after total splenectomy. The incidence of thrombocytosis was 41.0% (64/156). Thrombocytosis was more likely following splenectomy compared with spleen preserving strategies independent of length of stay, injury grade, ISS, age and transfusion (OR 7.58, 95% CI: 2.26–25.45). Splenectomy was associated with extreme thrombocytosis (OR 10.39, 95% CI: 3.59–30.07). Conclusions: Thrombocytosis in splenic trauma is more likely after splenectomy than with spleen preserving strategies. Splenectomy is associated with extreme thrombocytosis. There was insufficient data in our study to determine the use of ASA as primary prevention of VTE after splenic trauma.